2018
DOI: 10.1534/genetics.117.300634
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Drosophila Mei-41/ATR Alters Meiotic Crossover Patterning

Abstract: Meiotic crossovers must be properly patterned to ensure accurate disjunction of homologous chromosomes during meiosis I. Disruption of the spatial distribution of crossovers can lead to nondisjunction, aneuploidy, gamete dysfunction, miscarriage, or birth defects. One of the earliest identified genes involved in proper crossover patterning is , which encodes the ortholog of the checkpoint kinase ATR. Analysis of hypomorphic mutants suggested the existence of crossover patterning defects, but it was not possibl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…See S1 Table for data used for calculations. Statistical analyses of interference using χ 2 on 2-by-2 contingency tables of observed and expected DCOs [ 119 ], indicated that interference in the CR interval fell short of statistical significance between zim-1 and brc-1(tm1145); zim-1 , p = 0.064.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…See S1 Table for data used for calculations. Statistical analyses of interference using χ 2 on 2-by-2 contingency tables of observed and expected DCOs [ 119 ], indicated that interference in the CR interval fell short of statistical significance between zim-1 and brc-1(tm1145); zim-1 , p = 0.064.…”
Section: Resultsmentioning
confidence: 99%
“…Statistical analyses were performed using the two-tailed Fisher's Exact test, 95% C.I., as in [ 117 , 118 ]. For statistical analyses of interference we conducted χ 2 tests on 2-by-2 contingency tables of observed and expected DCOs [ 119 ].…”
Section: Methodsmentioning
confidence: 99%
“…If we look at other well-studied model eukaryotes, the centromere effect appears to be highly conserved and also very efficient in avoiding COs in pericentromeric regions. In Drosophila melanogaster the DSB landscape appears to be flat along the chromosome arm, but downstream recombination is then affected by the centromere effect that eliminates pericentromeric recombination intermediates and models the recombination pattern (Hatkevich et al, 2017;Brady et al, 2018). In maize the centromeric effect seems to work with a different mechanism but with the same result.…”
Section: Meiotic Recombination In Holocentric Plantsmentioning
confidence: 99%
“…ATR deletion in male mice causes fragmentation of the chromosome axis, and ATR is required for synapsis and loading of recombinases RAD51 and DMC1 at DSB sites [21,22]. In Drosophila , loss of Mei-41, the fly ATR orthologue, not only abrogates checkpoint signalling [23], but also alters the frequency and spatial distribution of COs [24]. In Arabidopsis thaliana , although atr mutants are fully fertile [25], ATR promotes meiotic recombination by regulating the deposition of DMC1 at DSBs [26].…”
Section: Introductionmentioning
confidence: 99%